Upper Gastrointestinal Fiberoptic Endoscopic Experience in Turkey - K. Bahri ATEŞ,; A. Remzi DALAY,; Sedat BOYACIOĞLU,; M. Emin CANER,; M. Enver DOLAR,; Fatih HİLMİOĞLU,; Burhan ŞAHİN, (Turkish Journal of Gastroenterology, 2020)
-